Mechanical properties of biomorphous ceramics - Kiselov, V.S.; Borisov, Yu.S.; Tryus, M.; Vitusevich, S.A; Pud, S.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Mechanical properties: The Vickers hardness and bending strength of porous biomorphic SiC (bioSiC) ceramics fabricated from different natural hardwoods were investigated. It has been found that these parameters are highly dependent on the geometrical densities of ceramics, and Vickers hardness values can be well described using the Ryskevitch-type equation. It has been shown that the data of geometrical density bio-SiC ceramics can be used to estimate mechanical parameters such as bending strength. Materials with advanced properties appropriate for surgical applications are being designed. Further ways to improve the mechanical properties of ceramics and ceramic products have been discussed